2012
DOI: 10.2136/sssaj2012.0100
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Benchmark Soils of Oklahoma

Abstract: Natural background concentrations of trace elements in soils must be determined to establish baseline levels for soil remediation and to avoid the establishment of inaccurate or unrealistic guideline levels. The objectives of this study were to establish the background total trace element concentrations including As, Cd, Cr, Cu, Mn, Mo, Ni, Se, Pb, and Zn in 28 Oklahoma benchmark soils and to determine the relationship between soil properties and natural trace element concentrations. Soil samples were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
(40 reference statements)
3
14
1
Order By: Relevance
“…In the present study, path analysis confirmed the results of the multiple regressions but in some cases allowed us to more specifically identify the soil property most related to carrot Pb uptake [11]. Both path analysis and stepwise multiple linear regression detected pH and CEC as soil properties affecting carrot Pb uptake.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, path analysis confirmed the results of the multiple regressions but in some cases allowed us to more specifically identify the soil property most related to carrot Pb uptake [11]. Both path analysis and stepwise multiple linear regression detected pH and CEC as soil properties affecting carrot Pb uptake.…”
Section: Discussionsupporting
confidence: 79%
“…Basta et al (1993) used path analyses to differentiate between the effects of pH, cation exchange capacity, and organic C on trace metal adsorption by two Iowa soils. Zhang et al (2005) and Richards et al (2012) used a path analysis to determine what soil chemical properties had the greatest impact on P adsorption and trace element content in 28 Oklahoma benchmark soils, respectively. Through path analyses, Tang et al (2007) showed how effective animal manure was in reducing Al toxicity in an acid soil, and Yan et al (2013) looked at manure effects on P sorption in a paddy soil.…”
mentioning
confidence: 99%
“…A pathway was also considered for error variance ( U ) of the metal absorption as the response variable not measured by the direct and indirect effects of predictor variables. Considering R 2 as the determination coefficient, the error variance in pathway analysis can be calculated following (Richards et al, 2012): U=1R2 Before using multiple linear regression and path analysis, the data were checked for normality. Data were log‐transformed where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…T he wide use of de‐icing salt (NaCl is most commonly used), heavy vehicular traffic on the wide streets in commercial land use zones in urban environment and the continual input of trace metals (Cu, Zn, Pb and Cd) to the urban soil adjacent to the streets (like tree pit soil) over time possibly are the main reasons of the elevated values of metals in urban soil (Kargar et al, 2013). Metal persistence in the environment, potential to bioaccumulate, and the mobility of Na and trace metals can make the contamination of urban soils with de‐icing salt and trace metals as an urban environmental problem (Richards et al, 2012).…”
mentioning
confidence: 99%